Healthy forests safeguard traditional wild meat food systems in Amazonia - André Pinassi Antunes; Pedro de Araujo Lima Constantino; Julia E. Fa; Daniel P. Munari; Thais Q. Morcatty; Michelle C. M. Jacob; Bruce W. Nelson; Mariana Franco Cassino; Elildo A. R. Carvalho; Amy Ickowitz; Lauren Coad; Richard E. Bodmer; et al. (Nature, 2025)
Abstract Amazonia is the largest 1 and the most species-rich tropical forest region on Earth 2 , where hundreds of Indigenous cultures and thousands of animal species have interacted over millennia 3,4 . Although Amazonia offers a unique context to appraise the value of wildlife as a source of food to millions of rural inhabitants, the diversity, geographic extent, volumes and nutritional value of harvested wild meat are unknown. Here, leveraging a dataset comprising 447,438 animals hunted across 625 rural localities, we estimate an annual extraction of 0.57 Mt of undressed animal biomass across Amazonia, equivalent to 0.34 Mt of edible wild meat. Just 20 out of 174 taxa account for 72% of all animals hunted and 84% of the overall biomass extracted. We show that this amount of wild meat can meet nearly half of protein and iron dietary requirements for rural peoples, along with a substantial portion of their needs for B vitamins (18–126%) and zinc (23%). However, wild meat productivity is likely to have decreased by 67% in nearly 500,000 km² of highly deforested areas of Amazonia. Furthermore, the availability of wild meat per capita decreases significantly in areas with higher human population, greater proximity to cities, and more extensive deforestation. These findings highlight the urgent need to preserve the forest to safeguard biodiversity and traditional wild meat food systems, which will be essential for ensuring Amazonian peoples’ well-being and achieving several of the United Nations Sustainable Development Goals 5 .